To what theories of laws of nature B. Faul’s argument is applicable? - T. S. Demin (Омский научный вестник: Серия "Общество. История. Современность")
The derivative argument of the consequences is aimed at proving the incompatibility of certain theories of the laws of nature in conjunction with physicalism and the existence of moral responsibility. In this text, it is outlined the applicability of this argument to the most famous theories of the laws of nature. The argument can only be directed to those theories that are pinched by realism regarding the laws of nature. This text demonstrates that the most promising targets for the argument are Armstrong’s theory as well as some of the nonreductive theories of the laws of nature